Capitalism, workers organising and the shifting meanings of workplace democracy. (26th May 2016) - Atzeni, Maurizio
Abstract: This article explores the limits imposed by a capitalist system of industrial relations on the construction of workplace democracy. It does so by focusing on the experiences of two grass-roots organisations, from both the formal and informal sectors of the economy, in the context of contemporary Argentina. Against one-sided and abstract views of union democracy, the article argues that, for a critical engagement on the issue of democracy, we should go beyond analyses that consider this in isolation from the material, institutional and ideological capitalist context within which unions' actions are inserted. Democracy permeates the life of unions as collective organisations, but the struggle for control in a context of unbalanced power shapes democracy as a practice. Questions about the right balance between democratic decision-making and delegation and between efficiency and accountability in unions remain open.